Shiga toxin-producing Escherichia coli O157 in beef and chicken burgers, and chicken carcasses in Buenos Aires, Argentina - Chinen, Isabel (2009)
Fil: Chinen, Isabel. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio Fisiopatogenia; Argentina.